2012
DOI: 10.1371/journal.pone.0036390
|View full text |Cite|
|
Sign up to set email alerts
|

Gaze Direction and Request Gesture in Social Interactions

Abstract: One of the most important faculties of humans is to understand the behaviour of other conspecifics. The present study aimed at determining whether, in a social context, request gesture and gaze direction of an individual are enough to infer his/her intention to communicate, by searching for their effects on the kinematics of another individual's arm action. In four experiments participants reached, grasped and lifted a bottle filled of orange juice in presence of an empty glass. In experiment 1, the further pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 35 publications
10
43
0
Order By: Relevance
“…Concerning request gestures, this was observed in previous studies where the authors found that the kinematics of reaching-grasping and placing and those of reaching-grasping and lifting were altered by the request gestures “give-me-in-the-hand” (Sartori et al, 2009), “feed-me” (Ferri et al, 2011) and “pour” (Innocenti et al, 2012). The fact that gestures understanding and responses preparing are interlaced processes also comes from a fMRI study (Newman-Norlund et al, 2007).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Concerning request gestures, this was observed in previous studies where the authors found that the kinematics of reaching-grasping and placing and those of reaching-grasping and lifting were altered by the request gestures “give-me-in-the-hand” (Sartori et al, 2009), “feed-me” (Ferri et al, 2011) and “pour” (Innocenti et al, 2012). The fact that gestures understanding and responses preparing are interlaced processes also comes from a fMRI study (Newman-Norlund et al, 2007).…”
Section: Introductionmentioning
confidence: 61%
“…Thus, we expected interference of the type of gesture with the actual action, which, however, could be stronger for request than symbolic gestures. The interference could induce movement slowing down or veering away from the gesturing conspecific (Tipper et al, 1991, 1997; De Stefani et al, 2012; Innocenti et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Joint attention relies on co-actors’ ability to monitor each other’s gaze and attentional states (Emery, 2000). For instance, when synchronizing actions, co-actors divide attention between locations relevant for their own and for their co-actor’s goal (Kourtis et al, 2014; see Böckler et al, 2012; Ciardo et al, 2016 for similar results using different tasks), and sharing gaze affects object processing by making attended objects motorically and emotionally more relevant (Becchio et al, 2008; Innocenti et al, 2012; Scorolli et al, 2014). Moreover, in a joint search task, co-actors who mutually received information about each other’s gaze location via different sensory modalities (i.e., vision, audition, and touch) searched faster than without such information (Brennan et al, 2008; Wahn et al, 2015).…”
Section: Sharing Sensorimotor Informationmentioning
confidence: 99%
“…Gaze is an important source of information about others' intentions and actions (Allison et al, 2000; Mennie et al, 2007; Becchio et al, 2008; Pierno et al, 2008; Sartori et al, 2009; Innocenti et al, 2012). From the gaze of another person, we can infer what the person is interested in, what she might desire, and, consequently, what she will do next (Pierno et al, 2006).…”
Section: Study 2: Spontaneous Perspective Taking Increases As Incongrmentioning
confidence: 99%
“…Participants were presented with brief videos (rather than still photographs) depicting two objects, a milk cartoon and a glass full of milk, on a table, with or without a person behind (see Figure 1). Because looking at an object often signals intention to act on the object (Allison et al, 2000; Mennie et al, 2007; Becchio et al, 2008; Pierno et al, 2008; Sartori et al, 2009; Innocenti et al, 2012), the tendency to take the actor's perspective should be stronger when the actor looks at one of the objects and even stronger when the actor reaches toward the object.…”
Section: Introductionmentioning
confidence: 99%